„Et ait: «Faciamus hominem ad imaginem et similitudinem nostram»” (Rdz 1, 26). Próba egzegezy bizantyńskiej na przykładzie Komentarza do Księgi Rodzaju Anastazego z Synaju - Jóźwiak, Magdalena (Vox Patrum, 2018)
The Hexaëmeron, traditionally ascribed to Anastasius of Sinai may be one of the most important works of Christian mysticism from the Byzantine era. Three factors make it especially significant. First, it is one of the longest and most detailed surviving examples of Christian mystical exegesis as practiced in the Byzantine period. Second, this commentary is an extensive and unified exposition of the theology of an important Church writer. And finally, the Hexaëmeron is not only steeped in biblical literature, but also contains a large reservoir of quotes and paraphrases of the early Church Fathers on the first three chapters of Genesis. In this article, I analyzed book VI of the Commentary to the Book of Genesis (PG 89, 921-938) by Anastasius of Sinai, in which Anastasius comments, inter alia, the verse from Genesis 1, 26. The main goal of my analysis was to answer the question whether Anastasius – the Byzantine exegete – in her exegesis of the Holy Scriptures, using the earlier considerations of the Fathers of the Church, is at least to a small extent original or uncritical rewrites the previous interpretations, not including any of these interpretations?